Evolução do crédito pessoal no Brasil e o superendividamento do consumidor aposentado e pensionista em razão do empréstimo consignado - Porto, Elisabete Araújo (2014)
This thesis revolves around the over-indebtedness of the retired and pensioner consumer because of the use of consigned credit. Its general objective is to analyze the emergence of this phenomenon in the context of the Brazilian consumer market, from public and economic policies that preceded it, some favoring it, and nature of the its problems consequences, especially in the elderly category, since the advent of consigned credit. For that is applied the deductive approach method, as well as the analytic, historical and interpretative methods, by means of bibliographic and documental research. The work studies the social and and economic factors which are sponsors of the exaggerated consume and leads to massive purchase. It culminates in the analysis of the called consigned-credit, which causes over-indebtedness of the retired and pensioners social categories, mostly hiper-vunerable elderly, approaching the financial institutions role in this panorama. It also analyses the respective solutions pointed by jurisprudence, doctrine and social sectors, in view of the absence of specific legislation, by use of inserts standards in Law No. 8,078, of September 11, 1990 (Code of Consumer Protection) and the others applicable laws, in an intersection between all known norms for dialogue of sources, in view of inexistence of specific legislation. The problematic analysis, under a ex lege perspective and following the parameters of the constitutionalized law, aims to contribute to a better understanding of indebtedness, with emphasis in the elderly consumer, and aspires to communicate the law professionals of some mechanisms to assist in forensic deal with that phenomenon, being subject of great current relevance.